2013
DOI: 10.1038/eye.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of systematic errors in intraocular pressure measurements on screening for ocular hypertension

Abstract: Aim Raised intraocular pressure (IOP) increases the risk of glaucoma. Eye-care professionals measure IOP to screen for ocular hypertension (OHT) (IOP421 mm Hg) and to monitor glaucoma treatment. Tonometers commonly develop significant systematic measurement errors within months of calibration, and may not be verified often enough. There is no published evidence indicating how accurate tonometers should be. We analysed IOP measurements from a population study to estimate the sensitivity of detection of OHT to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Error values vary and depend especially on the accuracy and reliability of the operator’s (ophthalmologist) work. These errors range from a few to several percents [105].…”
Section: Discussionmentioning
confidence: 99%
“…Error values vary and depend especially on the accuracy and reliability of the operator’s (ophthalmologist) work. These errors range from a few to several percents [105].…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the Blue Mountains Eye Study, it was shown that 34% of individuals with ocular hypertension (OHT) would be missed using a tonometer that underestimated IOP by 1 mm Hg. Conversely, 58% false-positive screening tests would occur using a tonometer that over-read by 1 mm Hg 5. Within-subject variation may also contribute.…”
Section: Introductionmentioning
confidence: 99%
“…B. nach LA-SIK, wo sich abhängig vom verwendeten Ablationsprofil noch weitaus größere Abweichungen ergeben können [19,20] oder etwa bei Keratokonus [21]. Eine Unsicherheit ergibt sich auch aus den zahlreichen, mittlerweile gebräuchlichen Messverfahren für die zentrale Hornhautdicke, die nur bis zu einem gewissen Grad mit der von Kohlhaas [22]. In der klinischen Praxis wurden Kalibrierungsfehler von 1 bis 3 mmHg berichtet [23,24].…”
Section: Astigmatismusunclassified